2023
DOI: 10.1002/mp.16255
|View full text |Cite
|
Sign up to set email alerts
|

Silicone‐based materials with tailored MR relaxation characteristics for use in reduced coil visibility and in tissue‐mimicking phantom design

Abstract: Background:The development of materials with tailored signal intensity in MR imaging is critically important both for the reduction of signal from nontissue hardware, as well as for the construction of tissue-mimicking phantoms. Silicone-based phantoms are becoming more popular due to their structural stability, stretchability, longer shelf life, and ease of handling, as well as for their application in dynamic imaging of physiology in motion. Moreover, silicone can be also used for the design of stretchable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Additionally, the 3D-printed mask substrate had noticeable MRI signal on low-echo-time gradient-recalled echo imaging. While this did not obscure interpretation, future designs could use alternate 3D materials or incorporate doping the substrate with paramagnetic materials to reduce signal from the substrate (Motovilova et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the 3D-printed mask substrate had noticeable MRI signal on low-echo-time gradient-recalled echo imaging. While this did not obscure interpretation, future designs could use alternate 3D materials or incorporate doping the substrate with paramagnetic materials to reduce signal from the substrate (Motovilova et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups reported having successfully designed and developed flexible RF coils based on coaxial cables [14], screen-printed arrays [15][16][17], liquid metals [8,13,[18][19][20], and conductive polymers [21]. Major MRI vendors have also made significant efforts to produce commercially available lightweight coils that apply less pressure onto the patient compared to previous coil generations (AIR TM Coils from GE Healthcare [22], Contour Coils from Siemens [23], and Shape Coils from Canon [24]).…”
Section: Flexible Coil Designs and Related Requirementsmentioning
confidence: 99%
“…The DIW technique is favored due to its significantly easier fabrication as well as its reduced visibility in images-the coil array is much thinner (0.6 mm) and uses smaller amounts of polymer to produce. Anecdotally, we also propose to suppress the appearance of silicone polymer in MR images [47].…”
Section: In Vitro Imagingmentioning
confidence: 99%